2002
DOI: 10.1038/labinvest.3780441
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of CD46, CD55, and CD59 on Complement Activation After Immunotherapeutic Treatment of Cervical Carcinoma Cells with Monoclonal Antibodies or Bispecific Monoclonal Antibodies

Abstract: SUMMARY:The role of membrane-bound complement regulatory proteins (mCRP) in the protection of tumor cells in vivo against elimination by the immune system is still unknown. In this study the effect of expression of these mCRP by cervical cancer cells was investigated. In situ expression of mCRP was observed on cervical carcinomas, normal cervical epithelial cells, and the surrounding stroma. Deposition of C3 and C5b-9 was sporadically found on the tumor cells and the surrounding stroma. A low expression of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…This approach is aiming at combining the tissue-specificity of an anti-tumor mAb together with the CDC effects of an anti-CRP mAb. Such antibodies against Crry, CD59 and CD55 have shown promising results (118,(128)(129)(130)(131).…”
Section: Therapeutic Remarksmentioning
confidence: 99%
“…This approach is aiming at combining the tissue-specificity of an anti-tumor mAb together with the CDC effects of an anti-CRP mAb. Such antibodies against Crry, CD59 and CD55 have shown promising results (118,(128)(129)(130)(131).…”
Section: Therapeutic Remarksmentioning
confidence: 99%
“…115 CVF and C3b conjugated mAbs targeting the carcinoma antigen EpCAM-mediated higher C3 deposition and CDC of the colorectal carcinoma cell lines in vitro. 88,89 The same group demonstrated that b-glucan as adjuvant to mAbs activates CR3 on effector cells and results in CDCC (reviewed in ref. 116).…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 99%
“…In vitro data resulted in a 3-fold increase in complement activation. 88,90 The feasibility of this approach was tested in a rat model. In rodents, the expression of mCRPs is different compared with humans: CD46 and CD55 is mainly expressed in the testis, and an additional functional homolog Crry/p65, acting at the level of C3, was identified as the most important mCRP on tumor cells in rats.…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 99%
“…The use of bispecific mAbs that could specifically target mCRPs of cancer cells provides promising future results for mCRP-based immunotherapy. [23][24][25] Selectively down-regulating mCRP expression in tumors using cytokines or drugs other than antibodies may be another option because mCRPs expressed by colon cancer cells were reported to be regulated by tumor necrosis factor a, interleukin 1b, and interferon c. 26,27 In addition, by evaluating the expression of mCRPs, it may be possible to determine whether a patient is suitable for immunotherapy and to predict the response rate to treatment. Monitoring mCRP expression during the course of colon cancer could be important for evaluating disease progression and prognosis.…”
Section: Commentmentioning
confidence: 99%